Regional Training on Climate-Smart Agriculture, Soil Fertility Management, and Soil Health Monitoring in Eastern and Southern Africa - Ambaw, Gebermedihin; Recha, John W.M.; Gitau, Angela; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The regional training on Climate-Smart Agriculture (CSA), soil fertility management, and soil health monitoring in Eastern and Southern Africa (ESA) was organized under the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) initiative. This program aimed to enhance the capacity of agricultural professionals across ESA to address the pressing challenges of climate change, land degradation, and food insecurity through cutting-edge tools and inclusive approaches. The training equipped participants with comprehensive knowledge and practical skills in CSA, advanced soil health monitoring, and fertility management. It emphasized integrating geospatial tools, artificial intelligence, and machine learning for soil mapping and addressing policy and gender considerations to promote sustainable agricultural practices across varied agroecological zones. Key focus areas included fundamentals of CSA and its practical applications; advanced soil health monitoring techniques, including geospatial and digital soil mapping; policy advocacy for scaling CSA practices into regional and national frameworks; and gender mainstreaming to ensure inclusivity and equity in CSA initiatives. The training utilized a participatory and interactive approach, combining theoretical lectures, group discussions, and multimedia resources, such as YouTube links. Sessions were facilitated by experts in CSA, soil management, soil health monitoring, gender mainstreaming, environmental and natural resource management, and geospatial soil mapping using AI and machine learning. Integrating gender mainstreaming and policy-influencing dialogue will ensure all participants' comprehensive and hands-on learning experience. The training underscored the importance of enabling policies to scale CSA. Case studies showcased regional efforts, highlighting opportunities to integrate CSA into existing frameworks. Gender mainstreaming sessions addressed social inequities and empowered marginalized groups, ensuring inclusive CSA benefits. Participants are expected to champion CSA practices in their regions, contributing to increased agricultural productivity, improved soil health, and resilience to climate change. Scaling these efforts will require sustained policy support, investment in digital tools, and inclusive strategies to engage diverse stakeholders. This training marks a significant step towards building a climate-resilient agricultural sector in ESA by equipping professionals with the skills and knowledge to address climate and environmental challenges. 57 participants from 18 countries, including 25% women, participated in this training.